Pyrolytic-deoxygenation of triglycerides model compound and non-edible oil to hydrocarbons over SiO 2 -Al 2 O 3 supported NiO-CaO catalysts - Asikin-Mijan, Nurul; Lee, Hwei Voon; Marliza, Tengku Sharifah; Taufiq-Yap, Yun Hin (Elsevier, 2018)
Catalytic deoxygenation (DO) of triglycerides-based feeds to diesel-like fuel was investigated over NiO-CaO/SiO2-Al2O3 and NiO/SiO2-Al2O3 catalysts using semi-batch reactor under partial vacuum and inert N2 flow. The results showed that the bi-functional catalyst exhibited the highest DO activity with product selectivity toward diesel-like fuel n-(C13–C20). The catalytic process appeared to inhibit the occurrence of side reactions via neutralization of the strong acid sites. On the other hand, DO reaction under inert N2 flow has improved the deoxygenated product, which demonstrate that N2 flow condition has effectively removed the decarboxylation/decarbonylation gasses (CO2/CO) from poisoning the catalyst active sites. The high concentration of strong basic-acid sites of the catalyst is the main reason for increased C–C cleavage pathway, while milder acidic sites responsible for C–O cleavage pathway. High degree of unsaturated fatty acid in the feedstock has affected adversely the DO of triglycerides by accelerating the catalyst deactivation. The N2 flow condition, degree of unsaturated fatty acid in the feedstocks, acidity and basicity of the catalysts are important factors to improve DO activity as well as product selectivity.